PENINGKATAN HASIL BELAJAR SISTEM PEREDARAN DARAH MANUSIA MELALUI MODEL STAD BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS V SDN 075/VII KASANG MELINTANG - Yesi Ratnasari; Puput Wahyu Hidayat (STKIP Subang, 2026)
This research aims to improve learning outcomes on the Human Blood Circulation System through the Student Teams Achievement Division (STAD) cooperative learning model assisted by picture media in Class V students of SDN 075/VII Kasang Melintang. The low student learning outcomes were caused by conventional learning methods that were less engaging, resulting in passive student participation and inability to understand the material optimally. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects consisted of 28 fifth-grade students. Data collection was carried out through observation sheets, tests, and documentation. The results showed that the average student learning outcomes in Cycle I reached 68.93 with 64.29% classical completeness, and in Cycle II it increased to 80.36 with 89.29% classical completeness, exceeding the specified minimum completeness criterion of 70. Thus, the STAD model assisted by picture media can effectively improve student learning outcomes on the Human Blood Circulation System material at SDN 075/VII Kasang Melintang.